Prologue - Perera Lumbí, Juan Francisco (Revista Universitaria del Caribe, 2018)
This volume shares the compilation of 11 articles structured in 4 sections, which include in the first section of Education: 1) Innovations in the training of mathematics teachers for multicultural contexts. In the second section, History and current affairs of URACCAN the articles: 2) Higher, relevant and quality education: inclusion, diversity, human rights and social extension: experience of the intercultural community university; 3) The university and the effectiveness of community development: The promotion of community ownership in the Autonomous Regions of Nicaragua; 4) Experience of the CEIMM in Las Minas: Accompaniment to women in indigenous territories; 5) Impact of accompaniment work and political incidence and social extension, carried out by URACCAN- CEIMM, New Campus in the municipalities of Rama, Muelle de los Bueyes, El Ayote and Bocana de Paiwas, 2010-2013. In the third section: Gender and interculturality the articles: 6) Human rights and current racism in the migrations of Africanity; 7) Towards the articulation of state and indigenous law in cases of violence against women in the Caribbean Coast of Nicaragua; 8) Experience of the Center for Attention to Women, Children and Adolescents; 9) Intercultural Communication Policies. A perspective built from URACCAN. In the fourth section: Environment and Natural Resources the articles: 10) Methodology of territorial ordering in the RACCN, a contribution to development with identity; 11) The life improvement approach: An alternative of Japanese extension for rural development in Latin American countries.